Unusual bleeding from hepaticojejunostomy controlled by side-to-side splenorenal shunt: A case report. Issue 32 (August 2018) - Li, Meisheng; Li, Qinghan; Lei, Qiucheng; Hu, Jianyuan; Wang, Fengjie; Chen, Huanwei; Zhen, Zuojun
Abstract: Rationale: Ectopic variceal bleeding due to hepaticojejunostomy (HJ) is unusual and difficult to manage. Reports on the use of side-to-side splenorenal shunt for severe bleeding from varices at HJ anastomosis are lacking. Patient concerns: A 43-year-old man was admitted to our hospital with repeated episodes of hematemesis. He has a history of right hemihepatectomy with HJ reconstruction to the left hepatic duct for hilar cholangiocarcinoma. Two years after surgery, he presented with repeated episodes of hematemesis and underwent blood transfusion. Diagnoses: Imaging tests and endoscopic investigation failed to identify the bleeding source. When conservative management failed to control his bleeding, he underwent emergency laparotomy, which revealed hemorrhage from ectopic varices at the HJ anastomosis. Interventions: To arrest the bleeding, a side-to-side venovenal anastomosis was created between the splenic and left renal veins to form a shunt for decompression of the varices at the HJ anastomosis. Outcomes: After the surgery, the patient's symptoms ceased, and a no bleeding in the digestive tract was noted at 2-year follow-up. Lessons: The present patient is the first reported case of unusual bleeding from HJ controlled by a side-to-side splenorenal shunt. We believe this approach is a useful and effective surgical treatment for severe bleeding from varices at the HJ anastomosis.